PENGARUH MOTIVASI, PELATIHAN DAN FASILITAS KERJA TERHADAP KINERJA PEGAWAI DINAS PENDAPATAN DAERAH PROVINSI SULAWESI TENGAH - Wahyuni, Sri (Katalogis, 2014)
This research aims to know and analyze the effects of motivation, training and job facilities, simultaneously  and  partially  on  personnel’s  performance  at  Regional  Income  Office,  Central Sulawesi Province. There are 107 Respondents in this study that have been determined as the sample using census method. Analysis method used in this research is multiple linear regression. The results show that motivation, training and job facilities simultaneously peform positive and significant  effects  on  personnel’s  performance  at  Regional  Income  Office  Central  Sulawesi Province. Partially, motivation, training and job facilities also   perform positive and significant effects  on  personnel’s  performance.  Determination  coefficient  shows  adjusted  R-square  0,56,4 indicates that 56,40% of personnel’s performance has been affected by motivation, training and job facilities, meanwhile 43,6% is affected by other variables that are not investigated in this research.